TSO coordination and strategic behaviour: A game theoretical and simulation model study based on the German electricity grid - Franziska Flachsbarth; Anna Pechan; Martin Palovic; Matthias Koch; Dierk Bauknecht; Gert Brunekreeft (Constructor University Bremen, Bremen Energy Research (BER), 2024)
The electricity grid includes multiple network areas managed by different operators, with transmission system operators (TSOs) handling high-voltage areas and distribution system operators managing midto low-voltage areas. These areas are interconnected and synchronized, creating classical external effects where one operator's actions impact others. Recently, high voltage direct current (HVDC) lines have been introduced, offering operators greater flexibility and control over power flows compared to conventional alternating current (AC) lines, thereby reducing congestion and losses. However, HVDC lines can significantly affect neighbouring grids, potentially leading to strategic behaviour by network operators. This paper examines the strategic use of HVDC lines, using a model-based approach on projected 2030 market data in the German electricity system. It finds that without explicit coordination mechanisms most hours result in incentives for non-cooperative outcomes, with only three hours within one year showing incentives for a cooperative outcome. Despite lower overall system costs with cooperation, asymmetric distribution of cooperation benefits prevents long-term cooperation. Thus, cost-revenuesharing schemes are needed to promote cooperation and balance benefits.
Keywords: 330; TSO coordination; strategic behaviour; game theory; simulation